2009
DOI: 10.1089/ast.2009.0357
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Electrophoresis Analysis of Organic Amines and Amino Acids in Saline and Acidic Samples Using the Mars Organic Analyzer

Abstract: The Mars Organic Analyzer (MOA) has enabled the sensitive detection of amino acid and amine biomarkers in laboratory standards and in a variety of field sample tests. However, the MOA is challenged when samples are extremely acidic and saline or contain polyvalent cations. Here, we have optimized the MOA analysis, sample labeling, and sample dilution buffers to handle such challenging samples more robustly. Higher ionic strength buffer systems with pK a values near pH 9 were developed to provide better bufferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…The microdevices were prepared as previously described (Skelley and Mathies, 2003;Skelley et al, 2005Skelley et al, , 2006Skelley et al, , 2007Chiesl et al, 2009;Stockton et al, 2009aStockton et al, , 2009bStockton et al, , 2010 and will be briefly discussed here. A sacrificial layer of polysilicon was deposited on a 10 cm borofloat glass wafer.…”
Section: Microdevice Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…The microdevices were prepared as previously described (Skelley and Mathies, 2003;Skelley et al, 2005Skelley et al, , 2006Skelley et al, , 2007Chiesl et al, 2009;Stockton et al, 2009aStockton et al, , 2009bStockton et al, , 2010 and will be briefly discussed here. A sacrificial layer of polysilicon was deposited on a 10 cm borofloat glass wafer.…”
Section: Microdevice Fabricationmentioning
confidence: 99%
“…A 3 mm deep PDMS gasket with 4 mm diameter wells placed over the reservoir holes alleviates evaporative and hydrodynamic imbalance issues by allowing for loading of sample and buffer volumes up to 50 lL. A schematic of the microdevice can be found in previous publications (Chiesl et al, 2009;Stockton et al, 2009aStockton et al, , 2009b.…”
Section: Microdevice Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to remove unwanted ions would be to combine SCWE with a subsequent sublimation technique, where the extract is freeze-dried and the organics are sublimated [53]. Alternatively, the effect of ions on the analysis could be mitigated by dilution of the samples and the use of chelating agents in the separation media [54], or the inclusion of hardware in the extraction apparatus specifically for desalting of samples after extraction [52,53].…”
Section: Extraction Systemmentioning
confidence: 99%
“…In this regard, the Mathies laboratory demonstrated that amino acids could be successfully analyzed by ME-LIF without desalting by the incorporation of ethylenediaminetetraacetic acid in the separation buffer to counteract the effects of multivalent cations [54]. However, the addition of ethylenediaminetetraacetic acid in the separation buffer for analysis of chiral compounds has not yet been investigated.…”
Section: Challenges Of Mars: Power Supply Arcing and Reactive Soilmentioning
confidence: 99%